Assessment of Temporomandibular Joint Disorders and Related Factors in Patients at Tertiary Care Hospital - Iffat Alia, Sadia Hassan, Ali Farooq, Osama Khattak, Zahra Shafqat, Saba Ahmed (Pakistan Journal of Medical & Health Sciences, 2022)
Background and goals: Temporomandibular disorders (TMD) are the utmost communal disorders of the temporomandibular joint and its linked structures. The objective of the study was the epidemiological assessment of Temporomandibular joint disorders and associated factors. Study Design: A descriptive cross-sectional study. Place and Duration: In the Oral and Maxillofacial surgery department of Punjab Dental Hospital, Lahore for one-year duration from January 2021 to December 2021. Methods: This study comprises a sample of 400 young adults aged 15-40 years of age selected by cluster sampling technique. The surveyors finalized questionnaires and conducted clinical trials. The analysis of data was done with the Fisher exact tests and Chi-square. Results: The pervasiveness of Temporomandibular disorders in the considered sample was 43.8%. The most communal symptoms of TMD were muscle tenderness, clicking and tenderness of temporomandibular joint. The utmost common influencing aspects for TMD were clenching, early contact in the bruxism and protrusive movement. There was a clear preponderance of girls (68.6%) over boys (31.4%) (p = 0.001). Conclusion: Symptoms of TMD in adults were common with the apparent preponderance of women. Keywords: Adolescents, Epidemiology, Diseases of the Temporomandibular joints.